Advanced nutrient removal from surface water by a consortium of attached microalgae and bacteria: A review. (October 2017) - Liu, Junzhuo; Wu, Yonghong; Wu, Chenxi; Muylaert, Koenraad; Vyverman, Wim; Yu, Han-Qing; Muñoz, Raúl; Rittmann, Bruce
Graphical abstract: Highlights: Microalgae-bacteria consortium can remove nutrients through diversified pathways. Attached microalgae-bacteria consortium is promising in advanced nutrient removal. Cooperative interactions in consortium can boost the formation of a stable community. Algae-bacteria consortium can be implemented in multiple biofilm photobioreactors. Abstract: Innovative and cost-effective technologies for advanced nutrient removal from surface water are urgently needed for improving water quality. Conventional biotechnologies, such as ecological floating beds, or constructed wetlands, are not effective in removing nutrients present at low-concentration. However, microalgae-bacteria consortium is promising for advanced nutrient removal from wastewater. Suspended algal-bacterial systems can easily wash out unless the hydraulic retention time is long, attached microalgae-bacteria consortium is more realistic. This critical review summarizes the fundamentals and status of attached microalgae-bacteria consortium for advanced nutrient removal from surface water. Key advantages are the various nutrient removal pathways, reduction of nutrients to very low concentration, and diversified photobioreactor configurations. Challenges include poor identification of functional species, poor control of the community composition, and long start-up times. Future research should focus on the selection and engineering of robust microbial species, mathematical modelling of the composition and functionality of the consortium, and novel photobioreactor configurations.